Schatten class operators on exponential weighted Bergman spaces - Xiaofeng Wang; Jin Xia; Youqi Liu (Journal of Inequalities and Applications, 2023)
Abstract In this paper, we study Toeplitz and Hankel operators on exponential weighted Bergman spaces. For 0 < p < ∞ $0< p<∞ $ , we obtain sufficient and necessary conditions for Toeplitz and Hankel operators to belong to Schatten-p class by the averaging functions of symbols. For a continuous increasing convex function h, the Schatten-h class Toeplitz and Hankel operators are also characterized.